ACCOUNTING CONTROL IN COLLEGE FRATERNAL ORGANIZATIONS. - Hornberger, D. J. (The Accounting Review, 1926)
Abstract Since the origin of fraternity life in the U.S. colleges and universities, the proper method of financial control has been one of the most vexing problems. Prior to the last decade little constructive work had been done in producing a satisfactory routine which would be both practicable and at the same time sufficiently simple for the training, or lack there of, which the average fraternity treasurer possessed. In the past ten years, however, more and more attention to the question has been paid by college officials, officials of national groups and by the personnel of groups themselves and this has resulted in several interesting developments. This trend may be accounted for in several ways, but probably follows the general interest which has become manifest due to federal regulations, higher costs and other factors. There are several factors peculiar to fraternal accounting control which are not to be found in most other types of organizations. The personnel of the college fraternity is a rapidly changing one. This means that the average treasurer no more than has time to become efficient as a business manager and bookkeeper when he passes on and the next victim takes his place.